A preliminary study on visit density and crowding perceptions at FRIM's canopy walkway in Kepong, Selangor - Yahya, Noor Azlin; Awang, Suryani; Mohammad Afandi, Syamsul Herman; Ong, T.; Chew, Ming Yee (Department of Wildlife and National Parks (DWNP) Peninsular Malaysia, 2001)
Site surveys were conducted on users of a canopy walkway located in the grounds of the Forest Research Institute Malaysia (FRIM). Questionnaires were distributed to find out visitors' perceptions and preferences on visit density and crowding at the walkway. The results found that visitors expected to see a median of 13.5 people at the canopy walkway before their visits. Actual encounter had a median of 5.5 persons. Most of the visitors (a mode of 63.2%) perceived the number of visitors encountered to be normal. The majority of users (35.3%) indicated four people as the maximum number for comfortable visit. The study showed that encountered number of visitors was lesser (40.7%) than that was expected. Although visitors did not perceived the number of visitors on the walkway to be too many, visitors prefer to have a much smaller number around them for a comfortable visit. More than half of the users (51.5%) are willing to pay more than the current fees if less people were to share the canopy walkway experience at the same time.